Who ya gonna call? [technical support]. - Kushner, D. (IEEE spectrum)
Under the modest rubric of customer service, tech supporters sit on the other end of the phone, guiding panicky computer users-including their companies' own employees-through the inevitable pitfalls of their wares. Without them, all the revolutionary technology being deployed every day would soon grind to a halt. Despite the recent economic downturn, technical support workers are in hot demand.